The Role of Grandmother’s Grandparenting on Family Harmony: a Phenomenological Analysis - Nailul Fauziah; Suryanto Suryanto; Wiwin Hendriani (Universitas Ahmad Dahlan, 2020)
Grandparenting could have a positive and negative effect on family harmony. This study aims to better understand the influence of grandmother’s grandparenting role towards family harmony. This phenomenological study used data derived from interviewing and observing five participants. The data were analyzed using interpretative phenomenology. The findings of this study found nine themes: the meaning of grandchildren for grandmother, the reason of grandmothers parenting, grandmothers way of parenting, the effect of family’s social economics, the relationship of grandmothers with family members, grandmothers problem solving to overcome family conflict, grandmothers role in the family, the emotional bonding between grandmother and grandchildren, Grandmothers feelings while grandparenting. The grandmothers’ parenting role could positively and negatively influence family harmony, depending on the meaning of grandchildren for the grandmothers. When the grandmother could accept the grandchildren, it will make the grandmother happy and affect family harmony.